2021
DOI: 10.1515/ract-2021-1024
|View full text |Cite
|
Sign up to set email alerts
|

Optimal 18F-fluorination conditions for the high radiochemical yield of [18F]AlF-NOTA-NHS complexes

Abstract: 18F-fluorination using aluminum-fluoride ([18F]AlF) chelate technique has been reported to give a low-to-moderate radiochemical yield, between 5 and 20%. Therefore, the work described here outlines the optimum 18F-fluorination condition for the formation of [18F]AlF2+ and [18F]AlF-NOTA-NHS complex with the radiochemical yield (RCY) and purity (RCP) of more than 90% as a prerequisite step before proceeding with the radiopharmaceutical preparation using the [18F]AlF-bifunctional chelator technique. As well as be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…25,26 We modified the target vector palbociclib and chose 1,4,7-triazacyclononane-1,4,7-triacetic acid (NOTA) as the macrocyclic bifunctional chelator. 27 In this study, we reported a pioneering one-step 18 F-labeled palbociclib derivative ([ 18 F]AlF-NOTA-PBB) designed from NOTA-AlF chelation chemistry as a CDK4/6-specific tracer. Then, the biochemical properties of [ 18 F]AlF-NOTA-PBB were evaluated to determine its potential as a CDK4/6-specific PET tumor imaging agent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 We modified the target vector palbociclib and chose 1,4,7-triazacyclononane-1,4,7-triacetic acid (NOTA) as the macrocyclic bifunctional chelator. 27 In this study, we reported a pioneering one-step 18 F-labeled palbociclib derivative ([ 18 F]AlF-NOTA-PBB) designed from NOTA-AlF chelation chemistry as a CDK4/6-specific tracer. Then, the biochemical properties of [ 18 F]AlF-NOTA-PBB were evaluated to determine its potential as a CDK4/6-specific PET tumor imaging agent.…”
Section: Introductionmentioning
confidence: 99%
“…As the first 18 F-labeled CDK4/6-targeted radiotracer, 18 F-CDKi had some limitations, such as a low yield and multiple reaction and purification steps, which sets a technical barrier to its clinical promotion . Al 18 F chemistry has the advantages of less radiolabeling time and milder conditions and has gradually become a mature 18 F-labeling technique that is beneficial for combination with a kit in preclinical research or clinical promotion. , We modified the target vector palbociclib and chose 1,4,7-triazacyclononane-1,4,7-triacetic acid (NOTA) as the macrocyclic bifunctional chelator . In this study, we reported a pioneering one-step 18 F-labeled palbociclib derivative ([ 18 F]­AlF-NOTA-PBB) designed from NOTA-AlF chelation chemistry as a CDK4/6-specific tracer.…”
Section: Introductionmentioning
confidence: 99%